2018
DOI: 10.1158/2326-6066.cir-17-0550
|View full text |Cite
|
Sign up to set email alerts
|

CD16A Activation of NK Cells Promotes NK Cell Proliferation and Memory-Like Cytotoxicity against Cancer Cells

Abstract: CD16A is a potent cytotoxicity receptor on human natural killer (NK) cells, which can be exploited by therapeutic bispecific antibodies. So far, the effects of CD16A-mediated activation on NK cell effector functions beyond classical antibody-dependent cytotoxicity have remained poorly elucidated. Here, we investigated NK cell responses after exposure to therapeutic antibodies such as the tetravalent bispecific antibody AFM13 (CD30/CD16A), designed for the treatment of Hodgkin lymphoma and other CD30 lymphomas.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 53 publications
(67 reference statements)
5
91
0
3
Order By: Relevance
“…Inhibition of CD16 shedding through ADAM17 blockade may increase NK cell activation in the TME, thereby potentiating antibody treatments targeting NK cells (251,255,256). Sustaining this CD16 mediated activity may be especially important, as the Cerwenka group showed that NK cell engagement through CD16 might prime NK cells against cancers by providing them with memory-like effects (257).…”
Section: Mabs In Pre-clinical Development-targeting Tumor Antigens Fomentioning
confidence: 99%
“…Inhibition of CD16 shedding through ADAM17 blockade may increase NK cell activation in the TME, thereby potentiating antibody treatments targeting NK cells (251,255,256). Sustaining this CD16 mediated activity may be especially important, as the Cerwenka group showed that NK cell engagement through CD16 might prime NK cells against cancers by providing them with memory-like effects (257).…”
Section: Mabs In Pre-clinical Development-targeting Tumor Antigens Fomentioning
confidence: 99%
“…A bi-specific Ab-recognizing CS1-NKG2D, which comprises an anti-NKG2D scFv and an anti-CS1 scFv, showed enhanced cytotoxicity and cytokine production from NK cells and significantly prolonged their survival in a multiple myeloma xenograft NOD-SCID IL2γc−/− (NSG) mouse model (104). A novel CD30/CD16A tetravalent bispecific Ab (AFM13), which has a longer half-life compared with that of other bi-/trispecific Abs, is currently under evaluation in a phase II clinical trial to treat patients with relapsed/refractory Hodgkin's lymphomas (NCT03192202) (105,106).…”
Section: Potentiation Of Nk Cell Activity Using Bi-or Trispecific Kilmentioning
confidence: 99%
“…Importantly, most of these phenotypic changes were due to epigenetic modifications, providing a mechanism for altered signaling and function in adaptive NK cells compared to conventional NK cells. Although the signals and the molecular mechanisms responsible for the expansion of adaptive NK cells remain unknown, recent data suggest a critical role for CD16 . Under this scenario, CD16 engagement by anti‐HCMV antibodies may promote the differentiation and further maintenance of adaptive NK cells.…”
Section: Adaptive Nk Cells and Immune Surveillancementioning
confidence: 99%
“…Although the signals and the molecular mechanisms responsible for the expansion of adaptive NK cells remain unknown, recent data suggest a critical role for CD16. 163 Under this scenario, CD16 engagement by anti-HCMV antibodies may promote the differentiation and further maintenance of adaptive NK cells. Whether adaptive NK cells emerge in other scenarios where specific antibodies are chronically elevated either in health or disease remains to be determined.…”
Section: Adaptive Nk Cells and Immune Surveillancementioning
confidence: 99%